Linearization in ASM1 model for the solution of pollutants transport equations - Neyva Maria Lopes Romeiro; Rigoberto Gregorio Sanabria Castro; Sandra Mara Cardoso Malta (Semina: Ciências Exatas e Tecnológicas, 2008)
It is proposed to reduce the complexity existing in non-linear BIOMOC and ASM1 models using Taylor’s frst-order series expansion in the terms whose reactive processes are non-linear. One of the advantages of linear models is the conservation of non-linear model variables. However, the main characteristic of this methodology refers to the computational time obtained in the numeral simulations, which is much shorter than that concerning the non-linear model results. Numerical results are presented, showing the effciency, precision and solidity of the proposed technique in well-known cases in the literature, using the semi-discrete method of finite elements.